Using G-FAST to recognize emergent large vessel occlusion: a training program for a prehospital bypass strategy. (23rd July 2019) - Chiu, Yu-Chen; Tang, Sung-Chun; Sun, Jen-Tang; Tsai, Li-Kai; Hsieh, Ming-Ju; Lee, Chung-Wei; Jeng, Jiann-Shing; Lee, Yu-Ching; Chien, Yu-Chun; Wang, Yao-Cheng; Chiang, Wen-Chu; Ma, Matthew Huei-Ming
Abstract : Introduction: The shorter the time between the onset of symptoms and reperfusion using endovascular thrombectomy, the better the functional outcome of patients. A training program was designed for emergency medical technicians (EMTs) to learn the gaze-face-arm-speech-time test (G-FAST) score for initiating a prehospital bypass strategy in an urban city. This study aimed to evaluate the effect of the training program on EMTs. Methods: All EMTs in the city were invited to join the training program. The program consisted of a 30 min lecture and a 20 min video which demonstrated the G-FAST evaluation. The participants underwent tests before and after the program. The tests included (1) a questionnaire of knowledge, attitudes, confidence, and behaviors towards stroke care; and (2) watching 10 different scenarios in a video and answering questions, including eight sub-questions of G-FAST parameters, and choosing a suitable receiving hospital. Results: In total, 1058 EMTs completed the training program. After the program, significant improvement was noted in knowledge, attitudes, and confidence, as well as scenario judgement. The performance of the EMTs in evaluating G-FAST criteria in comatose patients was relatively poor in the pre-test and improved significantly after the training course. Although the participants answered the G-FAST items correctly, they tended to overtriage the patients and refer them to higher-level hospitals. Conclusions: A short training program can improve the ability to identify stroke patients and choose a suitable receiving hospital. A future training program could put further emphasis on how to evaluate comatose patients and choose a suitable receiving hospital.